2021
DOI: 10.1007/s10006-021-01001-6
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the clinical utility of C-reactive protein and antibiotic use in patients undergoing major head and neck reconstructive surgery with outcome assessment

Abstract: Purpose This ambispective observational study aims to evaluate the local utility of peri-operative CRP testing and prophylactic antibiotics in relation to post-operative complications in patients who have undergone major head and neck oncological reconstructive surgery. Results A total of 79 patients were identified for inclusion; CRP testing was undertaken within the first 3 days postoperatively in 78/79 cases. Results demonstrated no benefit of extended prophylactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…19 20 An elevated CRP level is not a specific infectious reaction in the early postoperative period, and CRP has a delayed response that peaks 3 days after infective symptoms; some researchers have reported that CRP cannot be used as an isolated diagnostic marker in the early postoperative period. 21 22 Detecting fistulas on POD 2 to POD 3 may be difficult; however, if the postoperative course is complicated, CRP levels remain increased and may even increase to higher concentrations. 19 In this study, fistulas became clinically apparent, on average, by POD12, but the postoperative CRP levels in the “fistula” group were statistically higher than the “no-fistula,” starting from POD 2.…”
Section: Discussionmentioning
confidence: 99%
“…19 20 An elevated CRP level is not a specific infectious reaction in the early postoperative period, and CRP has a delayed response that peaks 3 days after infective symptoms; some researchers have reported that CRP cannot be used as an isolated diagnostic marker in the early postoperative period. 21 22 Detecting fistulas on POD 2 to POD 3 may be difficult; however, if the postoperative course is complicated, CRP levels remain increased and may even increase to higher concentrations. 19 In this study, fistulas became clinically apparent, on average, by POD12, but the postoperative CRP levels in the “fistula” group were statistically higher than the “no-fistula,” starting from POD 2.…”
Section: Discussionmentioning
confidence: 99%